2016
DOI: 10.1152/ajpgi.00328.2015
|View full text |Cite
|
Sign up to set email alerts
|

PAR2-dependent activation of GSK3β regulates the survival of colon stem/progenitor cells

Abstract: Protease-activated receptors PAR1 and PAR2 play an important role in the control of epithelial cell proliferation and migration. However, the survival of normal and tumor intestinal stem/progenitor cells promoted by proinflammatory mediators may be critical in oncogenesis. The glycogen synthase kinase-3β (GSK3β) pathway is overactivated in colon cancer cells and promotes their survival and drug resistance. We thus aimed to determine PAR1 and PAR2 effects on normal and tumor intestinal stem/progenitor cells and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(62 citation statements)
references
References 72 publications
2
60
0
Order By: Relevance
“…Furthermore, we demonstrated that these detrimental effects of thrombin are mediated by the activation of both PAR1 and PAR4, the two functional thrombin receptors. We have previously demonstrated that PAR1 is expressed in human and mouse colon crypts and organoids (Nasri et al ., ). The presence of PAR4 in stem cells/progenitors has not been previously demonstrated, but our results revealed an active role for PAR4 in these cells.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, we demonstrated that these detrimental effects of thrombin are mediated by the activation of both PAR1 and PAR4, the two functional thrombin receptors. We have previously demonstrated that PAR1 is expressed in human and mouse colon crypts and organoids (Nasri et al ., ). The presence of PAR4 in stem cells/progenitors has not been previously demonstrated, but our results revealed an active role for PAR4 in these cells.…”
Section: Discussionmentioning
confidence: 97%
“…This suggests that a compensatory mechanism might maintain the size of budding organoids in the presence of this high dose of thrombin, despite the anti‐proliferative effects induced by PAR1 activation. In a previous study, we observed that PAR1‐activating peptides increase the size of murine organoids in part by pushing differentiation processes (Nasri et al ., ). This could constitute the compensatory mechanism maintaining the size of budding organoids exposed to high doses of thrombin.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…83,84 On the other hand, β-arrestin2 does not associate with Akt downstream of PAR2, but forms a complex with PP2A/GSK3β in a Rho kinase dependent manner. 85 β-arrestin-PP2A-GSK3β signaling facilitates stem/progenitor cell survival in normal colon crypts and colon cancer. 85 …”
Section: β-Arrestin-dependent Signaling Via Scaffoldingmentioning
confidence: 99%
“…85 β-arrestin-PP2A-GSK3β signaling facilitates stem/progenitor cell survival in normal colon crypts and colon cancer. 85 …”
Section: β-Arrestin-dependent Signaling Via Scaffoldingmentioning
confidence: 99%